Postcolonial Dislocation and the Fragments of Belonging in Abdulrazak Gurnah’s Gravel Heart - S. Meena Abarajedha; Dr P. Pandia Rajammal (ILN Journal: Indian Literary Narratives, 2025)
This article offers a postcolonial analysis of Abdulrazak Gurnah’s Gravel Heart, focusing on the intertwined themes of dislocation, identity, and belonging. Gravel Heart is set in postcolonial Zanzibar and England, it portrays the life of Salim, a protagonist forced to leave his homeland, rendering him a refugee in his own country. Gurnah captures not only the physical aspect of displacement but also the deeper emotional and existential alienation that disconnects individuals from both their roots and their chosen environments. Using postcolonial perspective, this study explores how Gurnah portrays exile as a narrative of loss and a journey of reinvention. Salim's struggles reflect the fragmentation of ethnic identity and the challenges of forging a new life amidst political and familial betrayal. The findings reveal the novel's critique of colonialism's destructive legacy, which blocks the formation of personal and collective identities. Gurnah traces the characters' quest for memory, identity, and belonging while vividly illustrating the psychological and emotional effects of displacement via Salim's experiences. This paper demonstrates the significance of Gravel Heart in conversations about identity and migration and advances our understanding of the complex representation of exile in postcolonial literature.